Position-specific benchmarks for jump and reach metrics in the National Basketball Association Draft Combine - Ogata, H.; Henderson, F.; Yamashita, D. (International Journal of Strength and Conditioning, 2026)
This study analysed data from the NBA draft combine and aimed to establish position-specific normative data for jump and reach performance to support coaches in better assessing the jumping ability of basketball players. Data on body height with shoes, standing reach (STReach), vertical jump reach (VJReach), and running jump reach (RJReach) were obtained from publicly available sources for 1,048 players who participated in the NBA draft combine between the 2004-05 and 2022-23 seasons. Vertical jump height (VJHeight), running jump height (RJHeight), and run-up effect (RE) were calculated. These variables were then compared across five playing positions; point guard, shooting guard, small forward, power forward, and center and position-specific percentile scores were generated to create normative data. Results showed that RJReach significantly increased from guards to centers (p < .05), primarily reflecting positional differences in anthropometry. Notably, guards demonstrated significantly higher VJHeight, RJHeight, and RE (p < .05) compared to power forwards and centers, indicating that shorter players may compensate for their height through enhanced vertical jump and RE. Furthermore, height and STReach progressively increased from guards to centers, highlighting the contribution of anthropometric, non-trainable characteristics. VJReach and RJReach increased across positions, and this increase was significant between all positions but power forwards and centers. RE was higher in guards and forwards than in centers. These results imply that RE may capture unique, trainable aspects of jump performance. This study presents position-specific benchmarks for jumping ability, offering strength and conditioning coaches practical reference values to assess players` strengths and weaknesses and to design tailored training programs.